A new framework for the wind power curtailment and absorption evaluation. (2nd March 2016) - Sun, Can; Bie, Zhaohong; Zhang, Zijun
Summary: It is meaningful to study the wind power curtailments and absorption potentiality by considering different system states and time‐varying characteristics. In this research, a wind power restriction analysis model and a maximum wind power connection (WPC) analysis model are developed to assess the wind power curtailments subject to different constraints and explore the potential of wind power absorption. A Monte Carlo simulation‐based algorithm is utilized to evaluate the WPC in a hybrid power system. The proposed algorithms are solved by a MATLAB program with YALMIP and CPLEX. Based on two proposed models, advanced indices are proposed to measure the penetration level, the power curtailment, the potential of wind power absorption, and the utilization efficiency of wind power. The effectiveness of the proposed approach and indices is validated by a case study. The results indicate that the proposed method can discover the bottleneck of WPC and estimate the potential of absorbing additional wind power generation capacities in different buses, which is meaningful to determine ratings and locations for future wind farms. Copyright © 2016 John Wiley & Sons, Ltd.